Negative electrode and secondary battery
Patent Information
- Application Number
- JP2023142501
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-01
- Publication Date
- 2025-03-13
AI Technical Summary
【0010】 本発明によれば、レート特性が高い二次電池およびそれに用いる負極を提供することができる。
Smart Images

Figure 2025035453000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a negative electrode and a secondary battery. [Background technology]
[0002] In an electrode used in a lithium ion battery or the like, an active material layer is formed on a current collector. There are many methods for forming an active material layer on a current collector when producing an electrode, but they can be roughly divided into a wet method and a dry method from the viewpoint of whether or not the electrode mixture containing the active material is made into a slurry. In the wet method, an active material, a polymer, a solvent, etc. are mixed to obtain a slurry, and the obtained slurry is applied to a current collector and dried to form an electrode. On the other hand, in the dry method, an electrode is formed without going through a process of applying a solvent and an active material in a slurried state. For example, an electrode is formed by forming a granule containing an active material in advance and pressing it onto a current collector.
[0003] Patent Documents 1 and 2 disclose a technique in which granules containing an active material are formed in advance and then used to form an active material layer. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2015 / 029829 [Patent Document 2] JP 2020-129448 A Summary of the Invention [Problem to be solved by the invention]
[0005] In lithium ion secondary batteries, it is desirable to use electrodes that have excellent rate characteristics, that is, electrodes that can withstand high current charging and discharging, in order to meet the demand for rapid charging and discharging. In Patent Document 1, a lithium ion secondary battery is produced using negative electrode granules with a D50 of 70 μm and positive electrode granules with a D50 of 40 μm, but it was found that this lithium ion secondary battery does not have sufficiently good rate characteristics. In Patent Document 2, a positive electrode using granules with a D50 of 44.6 μm is disclosed, but it was found that even when a battery is produced using such granules, a battery with sufficiently good rate characteristics cannot be obtained.
[0006] As a result of investigations, the present inventors have found that in a negative electrode having an active material layer using a granule containing an active material including non-spherical particles, by appropriately adjusting the particle size distribution of the active material, a negative electrode in which there is little active material falling off from the current collector can be obtained, and a secondary battery including such a negative electrode has good rate characteristics.
[0007] The present invention has been made in consideration of the above circumstances, and provides an electrode (particularly a negative electrode) having an electrode (particularly a negative electrode) active material layer that has high adhesion to a current collector, and a secondary battery including the same. [Means for solving the problem]
[0008] That is, according to the present invention, there are provided the following electrodes and batteries. 1. A current collector; an active material layer provided on a surface of the current collector, the active material layer including an active material, a conductive additive, and a binder; A negative electrode comprising: the active material comprises non-spherical particles; The active material layer is composed of granules, A negative electrode, wherein in a volume-based particle size distribution of the granules measured by a laser diffraction / scattering method, D50 is more than 70 μm and not more than 120 μm, and the difference between D10 and D90 is 50 μm or more.
[0009] 2. A secondary battery in which the negative electrode described in 1 above and a positive electrode are stacked in multiple layers with a separator between them, optionally rolled up, and housed in an outer container, and a positive electrode terminal electrically connected to the positive electrode and a negative electrode terminal electrically connected to the negative electrode are extended from the outer container. Effect of the Invention
[0010] According to the present invention, it is possible to provide a secondary battery having high rate characteristics and a negative electrode used therein. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, an embodiment of the present invention will be described.
[0012] One embodiment of the present invention comprises: The negative electrode includes a current collector and an active material layer provided on a surface of the current collector, the active material layer including an active material, a conductive additive, and a binder. The active material includes non-spherical particles, The active material layer is composed of granules, The granules are characterized in that, in a volume-based particle size distribution measured by a laser diffraction / scattering method, D50 is greater than 70 μm and not greater than 120 μm, and the difference between D10 and D90 is 50 μm or more.
[0013] In one embodiment, the negative electrode is not particularly limited, but refers to a negative electrode used in a non-aqueous secondary battery material. The negative electrode is composed of a current collector and an active material layer provided on the surface of the current collector, and the active material layer contains an active material, a conductive assistant, and a binder, which are aggregated together. As the current collector, for example, a metal such as copper, nickel, titanium, or stainless steel can be used. As the current collector, it is preferable to use a flat metal, particularly a metal foil. The current collector will be described in detail later.
[0014] As the active material, a carbon-based active material can be used. As the carbon-based active material, natural graphite, artificial graphite, hard carbon, soft carbon, carbon black, or any mixture thereof can be selected. Natural graphite includes natural graphite with amorphous carbon coated on the particle surface, and similarly, artificial graphite includes artificial graphite with amorphous carbon coated on the particle surface. These natural graphite and artificial graphite can be used in the form of primary particles, particles in which primary particles are aggregated to form secondary particles, or mixtures thereof. In addition, the negative electrode active material may be a mixture of a carbon-based active material and a silicon-based active material. The negative electrode active material may include a metal material such as aluminum, lithium, silver, bismuth, calcium, cerium, indium, magnesium, tin, zinc, or nickel. The negative electrode active material will be described in detail later.
[0015] The conductive assistant is a material for reducing the resistance of the electrode. Examples of the conductive assistant include carbon black such as acetylene black and ketjen black, activated carbon, graphite, mesoporous carbon, fullerenes, carbon nanotubes, carbon nanofibers, carbon nanobrushes, and other carbon fibers. The conductive assistant will be described in detail later.
[0016] Examples of the binder include fluororesins such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), and polyvinyl fluoride (PVF), conductive polymers such as polyanilines, polythiophenes, polyacetylenes, and polypyrroles, synthetic rubbers such as styrene butadiene rubber (SBR), butadiene rubber (BR), chloroprene rubber (CR), isoprene rubber (IR), and acrylonitrile butadiene rubber (NBR), and polysaccharides such as carboxymethyl cellulose (CMC), xanthan gum, guar gum, and pectin. Also, examples of the binder that can be used include polyacrylic acid, polymethacrylic acid, lithium polyacrylate, sodium polyacrylate, potassium polyacrylate, sodium polymethacrylate, and potassium polymethacrylate; ethyl polyacrylate, ethyl polyacrylate, butyl polyacrylate, methyl polymethacrylate, ethyl polymethacrylate, butyl polymethacrylate, polyacrylamide, and polyacrylonitrile, and any mixtures thereof. Furthermore, as the binder, carboxymethylcellulose (hereinafter referred to as "CMC"), which is a derivative of cellulose, or a metal salt of carboxymethylcellulose (for example, sodium carboxymethylcellulose, potassium carboxymethylcellulose) can be used. The binder will be described in detail later.
[0017] In one embodiment, the active material layer is made of granules. The granules include an active material, a conductive additive, and a binder, and are aggregated together. In one embodiment, the granules have a volume-based particle size distribution measured by a laser diffraction / scattering method, in which D50 is more than 70 μm and 120 μm or less, and the difference between D10 and D90 is 50 μm or more. By appropriately adjusting the particle size distribution of the granules constituting the active material layer, the number of voids (paths) that connect from the current collector, which serves as a path for lithium ions, to the surface of the active material layer and the number of voids are maintained, thereby improving the rate characteristics of a secondary battery using the negative electrode of one embodiment.
[0018] In order for the granules constituting the active material layer to have a structure in which the above-mentioned particle size distribution is observed, it is preferable to first form granules in which the active material, the conductive assistant, and the binder are aggregated, and then stack the granules on the current collector to form the active material layer. The granules are granules (granulated material) obtained by aggregating the above-mentioned mixture of active material, conductive assistant, binder, and optionally a solvent. The active material layer used in the negative electrode of one embodiment is formed by applying the granules in which the active material, conductive assistant, and binder are aggregated to the surface of the current collector by a dry coating method. After the active material layer is formed in a state in which the granules are formed once, the pressing conditions can be adjusted to press the active material layer so as to obtain the desired density. When the active material layer is pressed, the granules gradually collapse, so that the active material layer is formed without eliminating the voids between the active material particles. Compared with an active material layer formed by a wet coating method using a slurry in which an active material, a conductive additive, and a binder are mixed, the active material layer in one embodiment formed using granules has a greater or equal number of pore paths in the thickness direction of the active material layer. The length of the pore paths can be adjusted by changing the pressing conditions such as the number of times and pressure of pressing while keeping the particle size of the active material and the amount of binder the same (i.e., using the same granules). Here, even in the case of an active material layer formed using granules, if the density is increased without adjusting the pressing conditions, the granules will be crushed back to the original state of active material particles, resulting in the active material being oriented, and the rate characteristics of a secondary battery using a negative electrode including such an active material layer will deteriorate.
[0019] Here, the average particle size of the granules is preferably more than 70 μm and not more than 120 μm. In one embodiment, the average particle size of the granules means the particle size at 50% of the integrated value in the volumetric particle size distribution measured by a laser diffraction / scattering method (median size: D50). Furthermore, in the volumetric particle size distribution of the granules measured by a laser diffraction / scattering method, the difference between D10 and D90 is preferably 50 μm or more.
[0020] From the viewpoint of optimal adhesion of the conductive assistant to the active material surface, the average particle size of the active material particles is preferably 1.0 μm or more, more preferably 1.5 μm or more, and even more preferably 2.0 μm or more. And, it is preferably 20.0 μm or less, more preferably 10.0 μm or less, and even more preferably 5.0 μm or less. In the present invention, the average particle size of the active material particles means the particle size at an integrated value of 50% (median size: D50) in the volume-based particle size distribution measured by a laser diffraction scattering method.
[0021] The negative electrode active material includes a carbon-based active material. The carbon-based active material is preferably natural graphite, artificial graphite, hard carbon, soft carbon, or any mixture thereof. Here, graphite is a carbon material having hexagonal plate-like crystals in a hexagonal system, and may be called graphite or the like. The natural graphite and artificial graphite include natural graphite coated with amorphous carbon, and artificial graphite coated with amorphous carbon.
[0022] Here, amorphous carbon refers to a carbon material that is amorphous as a whole and has a random network structure of microcrystals, which may have a structure similar to that of graphite in part. Examples of amorphous carbon include carbon black, coke, activated carbon, carbon fiber, carbon nanotubes, hard carbon, soft carbon, and mesoporous carbon. When using artificial graphite, it is preferable that the interlayer distance d value (d002) is 0.33 nm or more.
[0023] The crystal structure of artificial graphite is generally thinner than that of natural graphite. When artificial graphite is used as a negative electrode active material for a non-aqueous electrolyte secondary battery, particularly a lithium ion secondary battery, it is necessary that the artificial graphite has an interlayer distance that allows lithium ions to be inserted. The interlayer distance that allows lithium ions to be inserted and removed can be estimated by the d value (d002), and if the d value is 0.33 nm or more, lithium ions can be inserted and removed without any problems. In addition, the negative electrode active material may include a silicon-based active material (A) containing SiOx (wherein x is a number that satisfies 0.5≦x≦1.6) and a carbon-based active material.
[0024] The aspect ratio of the negative electrode active material is preferably 1.1 or more and 5 or less. When a granule is prepared that is mainly composed of a negative electrode active material having an aspect ratio in this range, the orientation of the active material layer can be easily adjusted by the pressing conditions, and the electrical characteristics of a secondary battery using a negative electrode having an active material layer with an adjusted orientation are stable. When the aspect ratio of the negative electrode active material is less than 1.1, the active material particles are packed too densely, making it impossible to adjust the orientation of the active material layer, and excellent rate characteristics cannot be obtained in a secondary battery using such a negative electrode. On the other hand, when a granule is formed using an active material with an aspect ratio of more than 5, if the pressing conditions are adjusted to obtain a desired density, the path length formed in the active material layer becomes too long, and the rate characteristics of a secondary battery using such a negative electrode tend to decrease no matter how much the orientation is adjusted. The orientation of the active material in the active material layer can be roughly estimated from the volumetric particle size distribution measured by a laser diffraction / scattering method. In the volumetric particle size distribution measured by a laser diffraction / scattering method of the granules constituting the active material layer, it is preferable that D50 is more than 70 μm and 120 μm or less, and the difference between D10 and D90 is 50 μm or more.
[0025] In one embodiment, when the entire granules are taken as 100 parts by mass, the content of the active material is preferably 95.0 parts by mass or more, more preferably 96 parts by mass or more, even more preferably 97 parts by mass or more, and preferably 99.5 parts by mass or less, more preferably 99.0 parts by mass or less, even more preferably 98.5 parts by mass or less. The proportion of the active material involved in the formation of the granules is at least 95% or more, preferably 97% or more, and even more preferably 99% or more.
[0026] The conductive assistant preferably contains at least one selected from the group consisting of carbon black, carbon nanofibers, and carbon nanotubes. The carbon black used as the conductive assistant preferably has an aggregate structure in which carbon nanoparticles are connected in a beaded shape. As the carbon black, acetylene black, ketjen black, etc. can be used. Carbon nanotubes formed of a substance composed of carbon atoms such as graphene into a cylindrical shape with a diameter of several nm and a length of several mm can also be used. In particular, single-walled carbon nanotubes formed in a substantially single layer around the cylinder or multi-walled carbon nanotubes formed in a multiple layer around the cylinder can be bundled.
[0027] In one embodiment, when the entire granule is taken as 100 parts by mass, the content of the conductive assistant is preferably 0.01 parts by mass or more, preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, even more preferably 3.0 parts by mass or more, and preferably 2.0 parts by mass or less, more preferably 1.5 parts by mass or less, and even more preferably 0.5 parts by mass or less.
[0028] In one embodiment, the granule further includes a binder. It is preferable that the conductive assistant and the binder are present on the surface and inside of the granule. In this way, when the granule is pressed, the pores between the active material particles are not crushed too much and the pores are not oriented too much, so that a desired density can be obtained.
[0029] The binder may include, for example, polyvinylidene fluoride (PVDF), polyvinylpyrrolidone (PVP), polytetrafluoroethylene, polyimide, polyamideimide, polyamide, styrene butadiene rubber (SBR), carboxymethyl cellulose (CMC), polyvinyl alcohol, polyvinyl butyral, or two or more of these, but is not limited to these, and can be changed appropriately depending on the solvent.
[0030] In one embodiment, when the entire granules are taken as 100 parts by mass, the content of the binder is preferably 0.5 parts by mass or more, more preferably 0.7 parts by mass or more, even more preferably 1.0 parts by mass or more, and preferably 5.0 parts by mass or less, more preferably 3.0 parts by mass or less, and even more preferably 2.0 parts by mass or less.
[0031] A method for manufacturing a negative electrode according to one embodiment preferably includes a step of forming granules by spraying and adding a dispersion liquid in which a conductive assistant is dispersed to the active material particles while mixing and stirring the active material particles, and a step of placing the granules on a current collector and pressing the granules. The method for forming the granules is not particularly limited, and examples of the method include a spray granulation method, an agitation granulation method, a fluidized bed granulation method, a rolling granulation method, an extrusion granulation method, and a compression granulation method. These granulation methods may be selected or combined as desired. An example of the spray granulation method is a spray drying granulation method. In the spray drying granulation method, for example, a dispersion liquid in which a negative electrode active material and a conductive assistant are dispersed is sprayed into a high-temperature gas in a spray dryer to perform granulation. In the agitation granulation method, for example, a dispersion liquid in which a conductive assistant is dispersed is sprayed and added to the negative electrode active material particles while mixing and stirring the negative electrode active material to perform granulation. By adjusting the number of presses and the pressure applied to the active material layer containing the granules thus formed, it is possible to obtain a desired electrode density while maintaining high adhesion between the current collector and the active material layer and maintaining the desired pore paths between the active material particles.
[0032] By attaching a dispersion containing a conductive assistant and a binder that have been highly dispersed in advance to active material particles without containing any other organic solvent, it is possible to prepare an active material with a conductive assistant uniformly formed on the surface. The diameter of the granules formed varies depending on the equipment used to mix and stir these materials, but it is possible to control the diameter by the amount and timing of spraying the dispersion of the conductive assistant and the binder, the mixing and stirring times, and other conditions. In addition, by classifying the formed granules through a sieve, it is possible to obtain granules with any particle size distribution.
[0033] In one embodiment, the material of the current collector is not particularly limited, but when the current collector is a positive electrode current collector, it is preferably aluminum foil. When the current collector is a negative electrode current collector, it is selected from the group consisting of copper, stainless steel, nickel, titanium, or an alloy thereof, and copper is particularly preferred. The shape of the current collector layer is not particularly limited, and may be foil, flat plate, or mesh. For example, the thickness is 0.001 mm or more and 0.5 mm or less.
[0034] When the granules are placed on the surface of the current collector or the surface of the current collector and pressed, the pressing method is not particularly limited as long as the electrode granules containing the electrode active material can be formed on the current collector. In one embodiment, it is preferable to use a roll-type pressure molding method. In the roll-type pressure molding method, a long current collector is arranged so that the current collector passes between a pair of rolls while the current collector is unwound from a roll body wound in a roll shape and wound up. The granules are supplied onto the current collector before passing through the rolls, and are compressed when passing between the rolls to form an electrode sheet. In order to adjust the supply amount of the granules, it is preferable to supply the thickness while smoothing the surface with a squeegee or the like before supplying them between the rolls. It is preferable to previously form a current collector surface layer containing a binder to enhance the binding property with the granules on the current collector foil. By adjusting the number of times of pressing the electrode sheet, the pressing pressure, the temperature, etc., it is possible to adjust the adhesion between the active material layer and the current collector and the length of the path of the voids between the active material particles.
[0035] A second embodiment of the present invention is a secondary battery in which the above-mentioned negative electrode and positive electrode are stacked in multiple layers with a separator interposed therebetween, optionally rolled up, and housed in an outer container, and a positive electrode terminal electrically connected to the positive electrode and a negative electrode terminal electrically connected to the negative electrode are drawn out from the outer container. The secondary battery according to the second embodiment can be produced using the above-mentioned negative electrode in accordance with a known method. In the second embodiment, the positive electrode is not particularly limited, but refers to a positive electrode used in a non-aqueous secondary battery material. For example, the positive electrode is composed of a positive electrode current collector and a positive electrode active material layer provided on the surface of the positive electrode current collector, and the active material layer includes a positive electrode active material, a conductive additive, and a binder. The positive electrode active material layer including the positive electrode active material, the conductive additive, and the binder can be formed on at least one surface of the positive electrode current collector. The positive electrode current collector can be made of stainless steel, aluminum, nickel, titanium, or a positive electrode current collector in which the surface of aluminum or stainless steel is surface-treated with carbon, nickel, titanium, or silver.
[0036] Positive electrode active materials include composite oxides of lithium and transition metals such as lithium-nickel composite oxide, lithium-cobalt composite oxide, lithium-manganese composite oxide, lithium-nickel-manganese composite oxide, lithium-nickel-cobalt composite oxide, lithium-nickel-aluminum composite oxide, lithium-nickel-cobalt-aluminum composite oxide, lithium-nickel-manganese-cobalt composite oxide, lithium-nickel-manganese-aluminum composite oxide, and lithium-nickel-cobalt-manganese-aluminum composite oxide; transition metal sulfides such as TiS2, FeS, and MoS2; MnO, V2O5, and V6O 13 , TiO2, or other transition metal oxides; and olivine-type lithium phosphate. The olivine-type lithium phosphate contains, for example, one or more elements selected from the group consisting of Mn, Cr, Co, Cu, Ni, V, Mo, Ti, Zn, Al, Ga, Mg, B, Nb, and Fe, lithium, phosphorus, and oxygen. These compounds may have some elements partially substituted with other elements in order to improve their properties. Among them, the positive electrode active material is Li a Ni b Mn c Co d M xIt is preferable to use lithium nickel manganese cobaltate represented by O2 (where a, b, c, d, and x satisfy 0.9 ≦ a ≦ 1.2, 0 < b < 1, 0 < c ≦ 0.5, 0 < d ≦ 0.5, 0 ≦ x ≦ 0.3, and b + c + d = 1, and M is at least one selected from the group consisting of Ti, Zr, Nb, W, P, Al, Mg, V, Ca, Sr, and Cr). Examples of the binder that forms the positive electrode and the material layer together with the positive electrode active material include fluororesins such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), and polyvinyl fluoride (PVF); conductive polymers such as polyanilines, polythiophenes, polyacetylenes, and polypyrroles; synthetic rubbers such as styrene-butadiene rubber (SBR), butadiene rubber (BR), chloroprene rubber (CR), isoprene rubber (IR), and acrylonitrile-butadiene rubber (NBR); or polysaccharides such as carboxymethyl cellulose (CMC), xanthan gum, guar gum, and pectin. Examples of the conductive assistant include carbon blacks such as acetylene black and ketjen black, activated carbon, graphite, mesoporous carbon, fullerenes, carbon fibers such as carbon nanofibers, carbon nanotubes, and carbon nanobrushes. In addition, electrode additives generally used for electrode formation, such as thickeners, dispersants, and stabilizers, can be appropriately used in the positive electrode active material layer.
[0037] In the secondary battery of the second embodiment, examples of the separator include porous separators. Examples of the form of the separator include membranes, films, nonwoven fabrics, etc. Examples of the porous separator include polyolefin-based porous separators such as polypropylene-based and polyethylene-based; porous separators formed of polyvinylidene fluoride, polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride hexafluoropropylene copolymer, etc.
[0038] The separator may contain inorganic particles such as ceramic particles or may further contain a layer containing inorganic particles.
[0039] In the secondary battery of the second embodiment, a negative electrode and a positive electrode are laminated with a separator therebetween, and may be wound and housed in an outer container. The secondary battery is formed by drawing out a positive electrode terminal electrically connected to the positive electrode and a negative electrode terminal electrically connected to the negative electrode from the outer container. For the outer container, for example, a flexible film having a resin layer on the front and back sides of a metal layer such as aluminum as a base material, or a can made of a metal such as aluminum, iron, or stainless steel can be used. The positive electrode terminal can be made of aluminum or an aluminum alloy, and the negative electrode terminal can be made of copper or a copper alloy or a copper alloy plated with nickel.
[0040] The shape of the secondary battery of the second embodiment may be, for example, a square, cylindrical, coin or button shape housed in an outer container using an aluminum can, an iron can, a stainless steel can, etc. Also preferred is a pouch-shaped secondary battery housed in an outer container mainly made of an aluminum film.
[0041] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above may also be adopted. Furthermore, the present invention is not limited to the above-described embodiments, and modifications and improvements within the scope of the present invention are included in the present invention. EXAMPLES
[0042] EXAMPLES Hereinafter, the present invention will be described with reference to examples and comparative examples, but the present invention is not limited to these.
[0043] <Production of negative electrodes> (Examples 1 to 4 and Comparative Examples 1 to 4) Separately from the formation of the conductive layer and the adhesive layer, granulated particles for the negative electrode active material layer were prepared. A negative electrode dispersion liquid was prepared by highly dispersing the negative electrode active material particles, which were artificial graphite with an average particle size of 12 μm and silicon monoxide with an average particle size of 5 μm, single-wall carbon nanotubes (SWCNT) as a conductive assistant, and polyacrylic acid (PAA) and styrene butadiene rubber (SBR) as binders together with a solvent. Next, the negative electrode dispersion liquid prepared by the above procedure was sprayed into a spray dryer by rotating the atomizer at a predetermined rotation speed to obtain a granule. The mass ratio of artificial graphite / silicon monoxide / CNT / PAA / SBR was 93.45:4.0:0.05:0.5:2.0. Artificial graphite from Nippon Graphite Industries Co., Ltd., PAA from Fujifilm Wako Pure Chemical Industries, Ltd., and SWCNT from OCSiAl Corporation can be used.
[0044] Next, a predetermined amount of the obtained granules was supplied onto a current collector traveling from the unwinding side to the winding side of the electrode coater while smoothing the surface with a squeegee. An adhesive auxiliary layer containing carbon black and binders (CMC and SBR) had been formed on the surface of the current collector in advance. After the granules were supplied onto the current collector, the amount of granules supplied to the press roll by the squeegee roll was adjusted before the granules were compressed by the press roll, and then the granules were passed between the press rolls to form an active material layer of the desired density. The volumetric particle size distribution of the granules constituting the active material layer, measured by the laser diffraction scattering method, is shown in Table 1. <Battery manufacturing> The positive electrode active material is LiNi with an average particle size of 4.5 μm. 0.92 Mn 0.03 Co 0.05 A slurry containing lithium nickel manganese cobalt oxide represented by O2, carbon black as a conductive additive, and polyvinylidene fluoride (PVDF) as a binder was applied to an aluminum foil as a positive electrode current collector, and then pressed to produce a positive electrode with a density of 3.5 g / cm. 3 A positive electrode of 1000 nm was obtained. The eight positive electrode layers and the nine negative electrode layers of each of the previously obtained Examples or Comparative Examples were laminated via a polyolefin-based porous separator, and a negative electrode terminal electrically connected to each negative electrode and a positive electrode terminal electrically connected to each positive electrode were provided to obtain a laminate. Next, an electrolyte solution in which LiPF6 was dissolved as an electrolyte in a mixed solvent of ethylene carbonate and diethyl carbonate (ethylene carbonate:diethyl carbonate=3:7 (volume ratio) to a concentration of 1.0 mol / L was placed together with the obtained laminate in a container with a flexible film as a case, and the container was sealed with the positive electrode terminal and the negative electrode terminal pulled out to the outside to obtain a secondary battery.
[0045] <Rate characteristics> The fabricated battery was charged at a constant current of 0.2C up to 4.2V, then switched to a constant voltage after reaching 4.2V and charged down to 0.015C, and discharged at constant currents of 0.2C and 3C down to 2.5V, and the rate characteristics were determined as 3C / 0.2C, which is the ratio of the capacity of the 3C discharge to the 0.2C discharge at 2.5V. Generally, the higher the current value, the more likely the capacity is to decrease, so the closer to 100%, the better the rate characteristics are.
[0046] <Measurement of particle size distribution by laser diffraction scattering method> The volumetric particle size distribution of the granules constituting the active material layer was measured by a dry particle size distribution measuring unit (LA-960 LY-9505, Horiba, Ltd.) using a laser diffraction scattering method. The D50 (median diameter), D10, and D90 were calculated from the particle size distribution curve (cumulative distribution curve) of the granules constituting each active material layer.
[0047] [Table 1]
[0048] As shown in Table 1, a secondary battery using a negative electrode with an active material layer having a particle size distribution of granules with a D50 of 80 to 120 μm exhibits good rate characteristics. On the other hand, a secondary battery using a negative electrode with an active material layer having a particle size distribution of granules with a D50 of 70 μm or less has low rate characteristics. As in Comparative Example 1, a negative electrode with an active material layer having a particle size distribution of granules with a D50 of 70 μm or less is likely to have voids that serve as ion paths, and it is considered that the rate characteristics of the secondary battery using this negative electrode are deteriorated. Even if a negative electrode with an active material layer having a granule particle size that is too large is used as in Comparative Example 2, a secondary battery with excellent rate characteristics could not be obtained. It can be inferred that this is because the large granules prevent the press density from being increased, which results in insufficient contact of the conductive assistant between the active material particles, and the battery cannot follow rapid charging and discharging. In addition, the granules constituting the negative electrode active material layer used in the secondary batteries of Comparative Example 3 and Comparative Example 4 had a small difference between D10 and D90 in the particle size distribution, i.e., the width of the particle size distribution was narrow. This made it difficult to obtain a desired active material layer density and difficult to adjust the paths of the voids present in the active material layer, presumably resulting in a deterioration in the rate characteristics of the secondary batteries.
[0049] The electrode for a lithium ion secondary battery and the lithium ion secondary battery of the present invention have been described in detail above. However, the present invention is not limited to the above-mentioned embodiments and examples, and various improvements and modifications may be made without departing from the spirit and scope of the present invention.
Claims
1. A current collector; an active material layer provided on a surface of the current collector, the active material layer including an active material, a conductive additive, and a binder; A negative electrode comprising: the active material comprises non-spherical particles; The active material layer is composed of granules, In a volume-based particle size distribution of the granules measured by a laser diffraction / scattering method, D50 is greater than 70 μm and not greater than 120 μm, and the difference between D10 and D90 is 50 μm or more.
2. The negative electrode according to claim 1 , wherein the granules are an aggregate of at least the active material, the conductive additive, and the binder.
3. The negative electrode according to claim 1 , wherein the aspect ratio of the active material is 1.1 or more and 5 or less.
4. A secondary battery comprising a negative electrode according to any one of claims 1 to 3 and a positive electrode stacked together with a separator therebetween, optionally wound, and housed in an outer container, and a positive electrode terminal electrically connected to the positive electrode and a negative electrode terminal electrically connected to the negative electrode being pulled out from the outer container.
Citation Information
Patent Citations
Manufacturing method of electrode for battery
JP2020129448A
Production method for granulated particles used in electrochemical element, electrode used in electrochemical element, and electrochemical element
WO2015029829A1